2005
DOI: 10.1177/17423953050010010101
|View full text |Cite
|
Sign up to set email alerts
|

A trial of asthma self-management in Beijing schools

Abstract: The programme provided overall benefits related to school performance, absences, and home environment. In the agricultural area, where fewer resources were available, benefits were fewer and concerns greater. In the industrial area, where education and income were higher, additional benefits related to healthcare use and parents' quality of life were realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Most studies relied on school records to identify absences. Five studies revealed that children who received the asthma education intervention had fewer absences than children who received usual care 17–19,26,32. In 1 study a reduction in school absences that approached statistical significance ( P = .07) was reported 28.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Most studies relied on school records to identify absences. Five studies revealed that children who received the asthma education intervention had fewer absences than children who received usual care 17–19,26,32. In 1 study a reduction in school absences that approached statistical significance ( P = .07) was reported 28.…”
Section: Resultsmentioning
confidence: 97%
“…Five studies revealed that asthma education was associated with statistically significant reductions in the mean number of days with asthma symptoms 15,16,18,20,34. For 6 studies no statistically significant differences in days with symptoms were reported 14,19,27,28,33,35…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Unfortunately, several studies that met all of the criteria for this review did not provide the data necessary for the computation of an effect size (e.g., Clark, et al, 2005;Jalan & Glinskaya, no date;Kremer, Moulin, & Namunyu, 2003).…”
Section: Criteria For Inclusion and Exclusion Of Studies In The Reviewmentioning
confidence: 99%